2018
DOI: 10.1002/ijop.12493
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child attachment as a mediator of the relationship between parenting style and gelotophobia among adolescents

Abstract: Fear of being laughed at and family interaction are highly related. Parental over-control and over-protection influence children's excessive anxiety over being laughed at. Conversely, parental attachment is an important index of the parent-child relationship and is closely correlated to children's gelotophobia. However, is it the style of parenting or the outcome of parenting (i.e. attachment) that influences a child's gelotophobia? To answer this question, the present study analysed the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…For a better understanding of the associations, we conducted a mini-meta-analysis (Goh, Hall, & Rosenthal, 2016) across data from both studies and found a mean correlation of r = .14 (95% CI = [.06, .22], z combined = 3.00, p = .003 [two-tailed]; N = 555) between katagelasticism and anxious attachment. This points toward a small positive association, as found in children and adolescents (e.g., Wu et al, 2015Wu et al, , 2019. The partner effects indicate that the dispositions are widely independent from their partners' attachment styles.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…For a better understanding of the associations, we conducted a mini-meta-analysis (Goh, Hall, & Rosenthal, 2016) across data from both studies and found a mean correlation of r = .14 (95% CI = [.06, .22], z combined = 3.00, p = .003 [two-tailed]; N = 555) between katagelasticism and anxious attachment. This points toward a small positive association, as found in children and adolescents (e.g., Wu et al, 2015Wu et al, , 2019. The partner effects indicate that the dispositions are widely independent from their partners' attachment styles.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, attachment was low in those with high expressions in the joy in laughing at others ( r = −.21/−.22), while the joy in being laughed at was unrelated to parental attachment (| r | < .12). The pattern was replicated in 101 children diagnosed with autism in Wu et al (2019). Again, katagelasticism was unrelated to memories of social support.…”
Section: Dispositions Toward Ridicule and Being Laughed Atmentioning
confidence: 85%
See 2 more Smart Citations
“…Overprotective and controlling parenting and anxiety: Lastly, there were 1 study that examined both the controlling and overprotective dimension of helicopter parenting simultaneously. This study found a relationship with anxiety (Wu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 77%